Le vivant, l’informe et le dégoût : Baudelaire, Flaubert et l’art de la (dé)composition - Florence Vatan (Flaubert: Revue Critique et Génétique)
Baudelaire and Flaubert were both interested in the issue of shapelessness and of its aesthetic challenges. In many respects, Baudelaire's poem "Une charogne" and Bouvard and Pécuchet's encounter with the putrid carcass of a dog are representative of an aesthetics of disgust. The depiction of shapeless and putrefying bodies, however, also becomes an exercise in formal mastery whose goal is to create beauty out of filth. In the case of Flaubert, the allusion to decomposing matter is intended to promote an aesthetic ideal of autogenesis that echoes Félix-Archimède Pouchet’s theories of spontaneous generation.